2009
DOI: 10.1007/s00423-009-0538-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk factors for mortality after relaparotomy: analysis of 254 patients

Abstract: Advanced age, the presence of either fever or hypothermia, and the need of mechanical ventilation are preoperative risk factors associated with mortality after relaparotomy and should be considered when planning reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 19 publications
4
27
0
6
Order By: Relevance
“…10 Although there was no indication in literature of the right time for the resurgery, it is common consensus that the earlier it is diagnosed, the better. 11 Relaparotomy due to rectus sheath hematoma was performed in 25% of the cases which is higher than reported by a study done in Sudan of 5.9% 14 but similar to a study in India which reported 21.28%. 15 Sepsis was seen in 11.1% of the cases in our study, and it was the main cause of mortality with both the patients who died succumbed to infections.…”
Section: Discussionsupporting
confidence: 66%
“…10 Although there was no indication in literature of the right time for the resurgery, it is common consensus that the earlier it is diagnosed, the better. 11 Relaparotomy due to rectus sheath hematoma was performed in 25% of the cases which is higher than reported by a study done in Sudan of 5.9% 14 but similar to a study in India which reported 21.28%. 15 Sepsis was seen in 11.1% of the cases in our study, and it was the main cause of mortality with both the patients who died succumbed to infections.…”
Section: Discussionsupporting
confidence: 66%
“…Studies from the general surgical literature have documented an increase in mortality after reoperation for postoperative complications . In LT, the impact of early reoperations on graft survival is still not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Relaparotomies are defined as abdominal operations performed following the initial surgery, usually within 60 days [6]. This includes any repeat operation, in which the skin incision is reopened for exploration.…”
Section: Introductionmentioning
confidence: 99%